2018
DOI: 10.1055/s-0038-1661379
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Untreated and Treated Anxiety and Depression to Prenatal, Intrapartum, and Neonatal Outcomes

Abstract: Objective  To determine independent perinatal associations of anxiety and depression in women who were and were not treated with psychotropic drugs in comparison to unaffected pregnancies. Study Design  From 2013 to 2014, 978 (6.3%) cases of anxiety/depression, of which 35% used psychotropic drugs, were compared with 14,514 (93.7%) unaffected pregnancies using logistic regression. Results  Subjects were more likely to be Non-Hispanic Whites, use tobacco and illegal substances, be unmarried, use public insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
3
26
0
1
Order By: Relevance
“…9 However, the overall PPH prevalence in our study was lower than that reported in other studies, as the registered estimates corresponded to the first 2 hours after delivery and not the first 24 hours postpartum. 10,12,34 The results of this national register-based study are in line with the latest meta-analysis on the topic, with a similar effect size for the reported association (RR 1.32) 35 but a lower one than the ones stated in other epidemiological studies (aOR 1.53-3.85), 10,18,20,34,36 possibly due to the exclusion from our population of pregnancies with inherent bleeding tendency. Another potential explanation for the slightly attenuated association observed could be that in other studies, the SSRI exposure was explored only during late gestation (versus at any time-point), probably including cases with more severe psychiatric illness and with a more amplified dose-response relationship than in our study.…”
Section: Discussionsupporting
confidence: 89%
“…9 However, the overall PPH prevalence in our study was lower than that reported in other studies, as the registered estimates corresponded to the first 2 hours after delivery and not the first 24 hours postpartum. 10,12,34 The results of this national register-based study are in line with the latest meta-analysis on the topic, with a similar effect size for the reported association (RR 1.32) 35 but a lower one than the ones stated in other epidemiological studies (aOR 1.53-3.85), 10,18,20,34,36 possibly due to the exclusion from our population of pregnancies with inherent bleeding tendency. Another potential explanation for the slightly attenuated association observed could be that in other studies, the SSRI exposure was explored only during late gestation (versus at any time-point), probably including cases with more severe psychiatric illness and with a more amplified dose-response relationship than in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The tryptophan metabolic pathway is important during pregnancy for fetal development, neuronal protection, and serotonin signaling. 71 Serotonin signaling deficiencies may be linked to depression or anxiety in pregnancy, and both maternal trauma history 72 and prenatal depression and anxiety [73][74][75] were associated with labor dysfunction in previous clinical investigations. In addition, serotonin stimulates uterine smooth muscle contractions in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and PTSD are associated with increased risks of preterm birth, low birth weight, and postpartum depression [57][58][59] and poor infant outcomes such as respiratory failure and low birthweight. [60][61][62] Women with a history of military service are also more likely to experience insufficient sleep compared with non-Veterans, possibly due to increased rates of PTSD or trauma history. 44 Sleep disorders have been linked to perinatal and maternal complications including preterm birth, preeclampsia, and gestational diabetes.…”
Section: Mental Health and Psychosocial Factorsmentioning
confidence: 99%
“…68 These experiences are also associated with mental health comorbidities including PTSD and depression, which in turn increase risk of adverse pregnancy outcomes. [60][61][62] A high proportion of women Veterans have also experienced sexual assault and trauma during their military service. In the VA health care system, military sexual trauma (MST) is defined as sexual assault or repeated, threatening sexual harassment during military service.…”
Section: Mental Health and Psychosocial Factorsmentioning
confidence: 99%